Preference of Generation Z Towards Social Interaction - Generose C. Billano; Jester John P. Cogollo; Eljan Michael C. Dela Cruz; Monica Lauren P. Manahan; Seith Nathaniel D. Romualdo; Tonette Jye T. Rizaldo; Sir Hassanal P. Abusma; Sir Mark F. Onia (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to determine the preferred mode of interaction of generation Z. There are four novelties: (1) To understand the percentage of students who prefer social media as a medium of social interaction, (2) To know the percentage of students who prefer face-to-face interaction, (3) To comprehend what medium do they prefer to use when they are discussing their courtship involvement, academic matters, personal issues, interpersonal relational conflicts, sex-related matters, and (4) To know the reasons for students' preference in terms of mode of Interaction. The study used a mixed-method approach, employed explanatory design, and used simple random sampling in choosing the 76 respondents/participants from the Sultan Kudarat State University (SKSU) students. A survey and an interview were conducted to compare face-to-face interaction and social media interaction as the primary mode of interaction. The results showed that 60 students prefer face-to-face interaction over 76 students, with a frequency of 78.94% out of 100%. It is concluded that most of the students prefer face-to-face social interaction rather than social media. This study has an impact on Generation Z, as it serves as a realization of their social activeness in interaction as well as on the community. Also, it will help society understand how Generation Z compares to other generations by being the generation most affected by technology and its rapidly evolving form of communication, as well as the loss of their ability to communicate.